2016
DOI: 10.1016/j.applthermaleng.2016.04.056
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis for the optimal location of a thin PCM layer in frame walls

Abstract: The thermal performance of building walls can be improved using phase change materials (PCMs). The objective of this study was to estimate the optimal location of a "thin" PCM layer to be incorporated into frame walls, parallel to the frame and insulation, for the purpose of increasing thermal mass and reducing peak heat fluxes across the wall. Based on a mathematical model built in this paper, it was found that an optimal location of this "thin" PCM layer can be estimated, and it was affected by the thermal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(42 citation statements)
references
References 21 publications
0
42
0
Order By: Relevance
“…It might vary from 5°C to 35 °C for different seasons, wall orientations and locations of the PCM layer. The optimal location of a thin PCM layer wallboard was estimated numerically by Jin et al [87,88].…”
Section: Numerical Studies For Building Wallsmentioning
confidence: 99%
“…It might vary from 5°C to 35 °C for different seasons, wall orientations and locations of the PCM layer. The optimal location of a thin PCM layer wallboard was estimated numerically by Jin et al [87,88].…”
Section: Numerical Studies For Building Wallsmentioning
confidence: 99%
“…It was found that an optimum location for PCM placement existed in terms of different thermal resistances between the PCM layers and the external thermal boundary conditions. Jin numerically optimized the location of the PCM layer under different parametric conditions by validating their model with experiments conducted using a dynamic wall insulator [10]. They presented that the optimum PCM layer location approaches the exterior surface of the wall when the melting temperature and the latent heat of PCMs were increased.…”
Section: Introductionmentioning
confidence: 99%
“…The proper location of the PCM in the structural components is a critical issue, and it determines the performance enhancement margins. In the literature, different locations for the PCM layer have been examined, for example, close to the exterior wall surface [7], close to the interior wall surface [8] and close to the intermediate insulation layer [9].…”
Section: Introductionmentioning
confidence: 99%